2016
DOI: 10.1038/srep26782
|View full text |Cite
|
Sign up to set email alerts
|

Structural Brain Alterations Associated with Rapid Eye Movement Sleep Behavior Disorder in Parkinson’s Disease

Abstract: Characterized by dream-enactment motor manifestations arising from rapid eye movement (REM) sleep, REM sleep behavior disorder (RBD) is frequently encountered in Parkinson’s disease (PD). Yet the specific neurostructural changes associated with RBD in PD patients remain to be revealed by neuroimaging. Here we identified such neurostructural alterations by comparing large samples of magnetic resonance imaging (MRI) scans in 69 PD patients with probable RBD, 240 patients without RBD and 138 healthy controls, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
88
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 54 publications
(102 reference statements)
13
88
1
2
Order By: Relevance
“…We used our standard image analysis pipeline to calculate DBM as a measure of brain alterations. This pipeline (Aubert-Broche et al, 2013) has been previously used for several multicenter and multi-scanner studies and it has been shown to produce robust results by removing site-specific biases (Boucetta et al, 2016;Sanford et al, 2017;Zeighami et al, 2015). Also, in an earlier study, we provided evidence that DBM was a more sensitive measure of atrophy than VBM, especially for subcortical areas (Zeighami et al, 2015).…”
mentioning
confidence: 61%
“…We used our standard image analysis pipeline to calculate DBM as a measure of brain alterations. This pipeline (Aubert-Broche et al, 2013) has been previously used for several multicenter and multi-scanner studies and it has been shown to produce robust results by removing site-specific biases (Boucetta et al, 2016;Sanford et al, 2017;Zeighami et al, 2015). Also, in an earlier study, we provided evidence that DBM was a more sensitive measure of atrophy than VBM, especially for subcortical areas (Zeighami et al, 2015).…”
mentioning
confidence: 61%
“…Likewise, patients with REM sleep behavior disorder, which generates dream-enacting motor activity during REM, show a volumetric decrement in the anterior lobes of the cerebellar cortex and cerebellar nuclei [67,68]. Vice versa, patients suffering from primary malfunctions of the cerebellum can show a variety of sleep disorders (for a detailed review, see [11,[69][70][71][72][73]).…”
Section: Sleep Disorders Can Lead To Cerebellar Malfunction and Vice mentioning
confidence: 99%
“…PD patients who experienced visual hallucinations had significant loss of GM volume in the lingual gyrus and superior parietal lobe compared to healthy controls and PD patients without visual hallucinations (Ramírez-Ruiz et al, 2007). PD patients with probable RBD showed volume loss in the pontomesencephalic tegmentum, medullary reticular formation, hypothalamus, thalamus, putamen, amygdala, and anterior cingulate cortex compared to healthy controls and PD patients without RBD (Boucetta et al, 2016). Structural cortical and subcortical changes in mesocortical and limbic reward-related areas have been observed in PD patients with ICDs.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 91%